2016
DOI: 10.1021/acsami.6b06932
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dispersion of Highly Pure Large-Diameter Semiconducting Carbon Nanotubes by a Flavin for Thin-Film Transistors

Abstract: Scalable and simple methods for selective extraction of pure, semiconducting (s) single-walled carbon nanotubes (SWNTs) is of profound importance for electronic and photovoltaic applications. We report a new, one-step procedure to obtain respective large-diameter s- and metallic (m)-SWNT enrichment purity in excess of 99% and 78%, respectively, via interaction between the aromatic dispersing agent and SWNTs. The approach utilizes N-dodecyl isoalloxazine (FC12) as a surfactant in conjunction with sonication and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 69 publications
(133 reference statements)
1
37
0
Order By: Relevance
“…[9,10] Due to the superiority of large-diameter s-SWCNTs,s orting them from commercial arc-dischargeSWCNTshas become aresearch hotspot. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, due to the strong van der Waals interaction between large-diameter s-SWCNTst hat is related to the low curvature of the nanotube wall, [27] those s-SWCNTsa re difficult to be dispersed and sorted, especially difficultt or ealize single-chirality sorting. Although many attemptsh aveb een reported to realize single-chirality selectivity towardl arge-diameters -SWCNTs with diameter greater than 1.3 nm, these methodss uffered from either the low sorting yield or the low purity.A se arly as in 2011, Ta nge, et al [28] reported that Poly (9,9-dioctylfluorene-alt-benzothiadiazole) (P8BT) tended to select (15,4) SWCNTsw ith ad iameter of 1.36 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] Due to the superiority of large-diameter s-SWCNTs,s orting them from commercial arc-dischargeSWCNTshas become aresearch hotspot. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, due to the strong van der Waals interaction between large-diameter s-SWCNTst hat is related to the low curvature of the nanotube wall, [27] those s-SWCNTsa re difficult to be dispersed and sorted, especially difficultt or ealize single-chirality sorting. Although many attemptsh aveb een reported to realize single-chirality selectivity towardl arge-diameters -SWCNTs with diameter greater than 1.3 nm, these methodss uffered from either the low sorting yield or the low purity.A se arly as in 2011, Ta nge, et al [28] reported that Poly (9,9-dioctylfluorene-alt-benzothiadiazole) (P8BT) tended to select (15,4) SWCNTsw ith ad iameter of 1.36 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the superiority of large‐diameter s‐SWCNTs, sorting them from commercial arc‐discharge SWCNTs has become a research hotspot . However, due to the strong van der Waals interaction between large‐diameter s‐SWCNTs that is related to the low curvature of the nanotube wall, those s‐SWCNTs are difficult to be dispersed and sorted, especially difficult to realize single‐chirality sorting.…”
Section: Introductionmentioning
confidence: 99%
“…S6 † presents the statistics for on/off ratio and carrier mobility of the s-SWNT TFTs. [25][26][27][28][29][30][31][32][33][34][35][36][37] For the random s-SWNT lm-based TFTs fabricated in our work, merely by plasma treatment, the devices were able to markedly outperform the previously reported random lmbased devices, and were even comparable with devices fabricated using aligned s-SWNT lms.…”
Section: Resultsmentioning
confidence: 56%
“…The dispersion exhibits greenish dark color, indicating successful dispersion of SWNT, as shown in the photograph of Figure 1a. The absorption spectrum of this sample (Figure 1b) displays this sample was enriched semiconducting SWNT according to the literature 8 . Figure 1c–e illustrate stepwise procedure to make a PMMA‐coated SWNT film.…”
Section: Figurementioning
confidence: 95%
“…SWNT film was prepared by a filtration of SWNT dispersion. For the preparation SWNT dispersion, plasma torched SWNT (diameter = 1.3 ± 0.3 nm, RN‐220 SWNTs, batch# R26‐036, NanoIntegris) was dispersed by using a sonochemical method (VCX 750, 40% power, 18.8 W/ml, probe tip diameter: 13 mm; Sonics & Materials) including FC12 as a surfactant, in p ‐xylene according to the previous literature (see Experimental in Supporting Information for detailed method) 7–9 . After centrifugation at 5000 g where g is gravitational acceleration, the 80% supernatant was collected.…”
Section: Figurementioning
confidence: 99%